Penegakan Peraturan Daerah Kota Sukabumi Nomor 1 Tahun 2022 Tentang Rancana Tata Ruang Wilayah dalam Pengelolaan Ruang Terbuka Hijau (RTH) di Kota Sukabumi - Wahyu Aji Saputra; Agus Rasyid Chandra Wijaya (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This research analyzes the enforcement of Sukabumi City Regional Regulation No. Law No. 1 of 2022 regarding the 2022–2042 Spatial Planning (RTRW) in the management of Green Open Space (RTH). By utilizing a qualitative approach, this research assesses the extent to which the regulations on green open space (RTH), particularly public RTH at 20% and private RTH at 10%, have been implemented. The findings show that the presence of public green open spaces is still far from the expected standard (5%), the existing law enforcement is inadequate, and community participation is still not optimal. Means include enhancing regulatory enforcement capabilities, strengthening cooperation among stakeholders (government, community, and private sector), and implementing a Monitoring and Evaluation system using geospatial technology.